Analisis Kualitas Pelayanan Publik pada Perusahaan Umum Daerah Air Minum Tirta Yapono Kota Ambon - Hallatu, Falen; Soselisa, Pieter Sammy; Sakir, Ahmad Rosandi (Jurnal Studi Pemerintahan dan Akuntabilitas, 2024)
Purpose: This study aims to explore and analyze the quality of public services provided by Perusahaan Umum Daerah Air Minum (PERUMDAM) Tirta Yapono in Ambon City. Research Methodology: A qualitative descriptive approach was employed, with 10 customers serving as key informants, along with 2 customer relations staff and 1 general affairs head. Data collection focused on understanding service quality based on five key dimensions. Results: The research identified five dimensions of service quality: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Across these dimensions, several issues were observed, revealing that the services provided have not fully met the quality standards. Many customers perceive the services as suboptimal, highlighting areas that require significant improvement to better meet customer needs. Limitations: The study focuses solely on PERUMDAM Tirta Yapono, which may limit the generalizability of the findings to other regions or sectors. Contribution: This research underscores the need for improvements in the quality of public services within PERUMDAM Tirta Yapono, providing a foundation for developing strategies to enhance customer satisfaction and service delivery standards.